A review on the recent developments of solution processes for oxide thin film transistors. (8th May 2015) - Ahn, Byung Du; Jeon, Hye-Ji; Sheng, Jiazhen; Park, Jozeph; Park, Jin-Seong
Abstract: This review article introduces the recent advances in the development of oxide semiconductor materials based on solution processes and their potential applications. In the early stage, thin film transistors based on oxide semiconductors fabricated by solution processes used to face critical problems such as high annealing temperatures (>400 °C) required to obtain reasonable film quality, and the relatively low field effect mobility (<5 cm 2 V −1 s −1 ) compared to devices fabricated by conventional vacuum-based techniques. In order to overcome such hurdles, the proper selection of high mobility amorphous oxide semiconductor materials is addressed first. The latter involves the combination of high mobility compounds and multilayered active stacks. Ensuing overviews are provided on the selection of optimum precursors and alternative annealing methods that enable the growth of high quality films at relatively low process temperatures (<200 °C). Reasonably high field effect mobility values (~10 cm 2 V −1 s −1 ) could thus be obtained by optimizing the above process parameters. Finally, potential applications of solution processed oxide semiconductor devices are summarized, involving, for instance, flexible displays, biosensors, and non-volatile memory devices. As such, further innovations in the solution process methods of oxide semiconductor devices are anticipated to allow the realization of cost effective, large area electronics in the near future.